Pembesaran Lele Dalam Drum dan Pemanfaatan Limbah Lele Pada Tanaman Kangkung dan Tabulampot di Desa Tegalboto, Kecamatan Sumbersari, Kapubaten Jember - Atok Ainur Ridho; Insan Wijaya; Bagus Tripama (Journal of Community Development, 2021)
Branch of Muhammadiyah Tegalboto Kidul is a forum for Muhammadiyah da'wah activities within the scope of the village level. Muhammadiyah's space for movement is not only in religious activities, but in social, economic and other fields. The activity program of the Muhammadiyah branch of Tegal Boto Kidul which has been running so far is only in the routine study of recitation and social movements such as compensation for the needy. Activities related to economic development in branch members in particular and the surrounding community have generally not been carried out much. The purpose of this community service is to provide education to the community as a solution to limited land owned but still able to carry out fish farming and vegetable and fruit farming activities. This service aims to optimize the narrow land with a fish farming system in small media, does not require large areas, is cheap, is easily available media and technology that can be carried out by all groups of society at large. This service is expected to be a solution to the problem of limited land for fish cultivation, especially in cities, the problem of decreasing the availability of aquaculture and the problem of the need for fish animal protein in the community. The implementation of this community activity has been carried out during pandemic Covid-19 in Tegalboto Village, Sumbersari District, Jember Regency, including counseling, education and training on “budidakmber”, measuring the quality of cultivated water, measuring the weight of catfish.